Promoting integrated blue–green infrastructure for urban resilience—lessons learned from case studies - Jagadisan, Sharmila (Frontiers in Water, 2024)
In recent years, the climate change crisis has become a serious concern and has heightened public perceptions of environmental awareness and the importance of ecological sustainability. Human-induced climate change poses a grave and dangerous threat to our entire ecosystem. Climate change profoundly impacts all life on Earth, driven by the overexploitation of resources and unsustainable choices. This threatens our health, security, and survival. Blue–green infrastructure presents significant opportunities to address complex multifaceted urban concerns, including global temperature rises and biodiversity loss. This research focuses on how blue–green spaces play a crucial role in minimizing the cascading risks through nature-based solutions as an efficient approach to managing natural resources sustainably. It also explores how the integrated blue–green infrastructure projects benefit human wellbeing and increase the livability quotient. This research utilizes a wide range of evidence to demonstrate how various global case studies involved in blue–green infrastructure (BGI) projects positively impact health and social cohesion. This study has important implications for policymakers and urban planning practitioners and can potentially help decision-makers prioritize more holistic and socially inclusive BGI projects.